Can health and social care integration make long-term progress? Findings from key informant surveys of the integration Pioneers in England. Issue 1 (25th October 2019) - Erens, Bob; Wistow, Gerald; Mays, Nicholas; Manacorda, Tommaso; Douglas, Nick; Mounier-Jack, Sandra; Durand, Mary Alison
Abstract : Purpose: All areas in England are expected by National Health Service (NHS) England to develop integrated care systems (ICSs) by April 2021. ICSs bring together primary, secondary and community health services, and involve local authorities and the voluntary sector. ICSs build on previous pilots, including the Integrated Care Pioneers in 25 areas from November 2013 to March 2018. This analysis tracks the Pioneers' self-reported progress, and the facilitators and barriers to improve service coordination over three years, longer than previous evaluations in England. The paper aims to discuss these issues. Design/methodology/approach: Annual online key informant (KI) surveys, 2016–2018, are used for this study. Findings: By the fourth year of the programme (2017), KIs had shifted from reporting plans to implementation of a wide range of initiatives. In 2018, informants reported fewer "significant" barriers to change than previously. While some progress in achieving local integration objectives was evident, it was also clear that progress can take considerable time. In parallel, there appears to have been a move away from aspects of personalised care associated with user control, perhaps in part because the emphasis of national objectives has shifted towards establishing large-scale ICSs with a particular focus on organisational fragmentation within the NHS. Research limitations/implications: Because these are self-reports of changes, they cannot be objectively verified. Later stages of the evaluation will look at changes in outcomes and user experiences. Originality/value: The current study shows clearly that the benefits of integrating health and social care are unlikely to be apparent for several years, and expectations of policy makers to see rapid improvements in care and outcomes are likely to be unrealistic.